2004
DOI: 10.1021/ef049858q
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure−Property Relationships for Melting Points and Densities of Ionic Liquids

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
128
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(131 citation statements)
references
References 26 publications
1
128
1
1
Order By: Relevance
“…[17][18][19][20][21] [8,9] Andererseits argumentiert Hunt mithilfe quantenchemischer Rechnungen, dass die Erhöhung von Schmelzpunkten und Viskositäten durch C(2)-Methylierung von der verringerten Entropie herrührt. [5,6] Erst kürzlich zeigten Noack et al, dass weder die "Defekt-Hypothese" von Fumino et al noch die "Entropie-Hypothese" von Hunt allein die ¾nderungen der physikalisch-chemischen Eigenschaften erklären können.…”
unclassified
“…[17][18][19][20][21] [8,9] Andererseits argumentiert Hunt mithilfe quantenchemischer Rechnungen, dass die Erhöhung von Schmelzpunkten und Viskositäten durch C(2)-Methylierung von der verringerten Entropie herrührt. [5,6] Erst kürzlich zeigten Noack et al, dass weder die "Defekt-Hypothese" von Fumino et al noch die "Entropie-Hypothese" von Hunt allein die ¾nderungen der physikalisch-chemischen Eigenschaften erklären können.…”
unclassified
“…N is the Avogadro number and W the molecular weight. In a different study, Trohalaki et al [83] used heuristic methods based in several linear regressions to obtain the density of triazolium bromides, the descriptors were used in order to represent the degree of electrostatic interaction and the relation between the surface charge associated to hydrogen bridges and the total surface. Valderrama et al [84] reported a semi-empirical linear model based on empirical parameters and boiling points that can help for the determination of ILs density values at different temperatures.…”
Section: Relationship Between Structure and Densitymentioning
confidence: 99%
“…Such strategies may also be of interest for designing energetic materials. Approximately 10 18 different ionic liquids are possible (Trohalaki et al, (2005)). …”
Section: General Description Of Ionic Liquids (Ils)mentioning
confidence: 99%